2020
DOI: 10.3390/antibiotics9090539
|View full text |Cite
|
Sign up to set email alerts
|

Ibrexafungerp: A Novel Oral Triterpenoid Antifungal in Development for the Treatment of Candida auris Infections

Abstract: Candida auris is an emerging multidrug-resistant fungal pathogen reported worldwide. Infections due to C. auris are usually nosocomial and associated with high rates of fluconazole resistance and mortality. Echinocandins are utilized as the first-line treatment. However, echinocandins are only available intravenously and are associated with increasingly higher rates of resistance by C. auris. Thus, a need exists for novel treatments that demonstrate potent activity against C. auris. Ibrexafungerp is a first-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 55 publications
0
33
0
1
Order By: Relevance
“…It also showed consistent activity against C. glabrata with fks mutations, which confer resistance to echinocandins, with MIC values ranging from <0.03 to 4 μg/ml ( Nunnally et al., 2019 ). Additionally, ibrexafungerp has uniform and potent activity against C. auris , an emerging multidrug-resistant fungus, which was demonstrated in several studies ( Berkow et al., 2017 ; Arendrup et al., 2020 ; Barat SB-E, 2020 ; Ghannoum et al., 2020a ). Furthermore, ibrexafungerp has also shown the ability to reduce C. auris tissue fungal burden in an in vivo guinea pig model ( Ghannoum et al., 2020b ).…”
Section: Ibrexafungerpmentioning
confidence: 91%
See 2 more Smart Citations
“…It also showed consistent activity against C. glabrata with fks mutations, which confer resistance to echinocandins, with MIC values ranging from <0.03 to 4 μg/ml ( Nunnally et al., 2019 ). Additionally, ibrexafungerp has uniform and potent activity against C. auris , an emerging multidrug-resistant fungus, which was demonstrated in several studies ( Berkow et al., 2017 ; Arendrup et al., 2020 ; Barat SB-E, 2020 ; Ghannoum et al., 2020a ). Furthermore, ibrexafungerp has also shown the ability to reduce C. auris tissue fungal burden in an in vivo guinea pig model ( Ghannoum et al., 2020b ).…”
Section: Ibrexafungerpmentioning
confidence: 91%
“…Ibrexafungerp (formerly SCY-078) is the first compound of the enfumafungin-derived triterpenoid class of antifungals and the first oral (1-3)-β-D-glucan synthase inhibitor (GSIs) ( Ghannoum et al., 2020a ). GSIs are a group of drugs that act by inhibition of β-1,3-D-glucan synthase, a key enzyme in the biosynthesis of ß-(1,3)-D-glucan, a major component of the fungal cell wall.…”
Section: Ibrexafungerpmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, Chaturvedi et al reported that Ibrexafungerp was efficient against pan-resistant (defined as in vitro resistance to two or more azoles, all echinocandins and amphotericin B) C. auris isolates from the outbreak in New-York [98] and Ghannoum et al demonstrated that it was active to control skin infection and colonization of hospitalized patients [99]. Recently, a review compiled data on Ibrexafungerp, established it is a promising, new antifungal agent to treat C. auris infections, as patients experienced a complete response after treatment [100]. From a chemical point of view, SCY-078 is based on a lipophilic tetracyclic-fused core with addition of protonable nitrogen moieties (pyridine, triazole and primary amine).…”
Section: In Vitro Screening and In Vivo Validationmentioning
confidence: 99%
“…In Vitro studies demonstrate significant activity against most common Candida species including several resistant strains such as Candida glabrata and Candida auris ( Schell et al., 2017a ; Ghannoum et al., 2020 ). Moreover, it demonstrates excellent in vitro activity versus both wild-type and azole-resistant strains of Aspergillus ( Lamoth and Alexander, 2015 ).…”
Section: Ibrexafungerp (Scynexis Formerly Scy-078)mentioning
confidence: 99%